Globalisation: its philosophical and sociological presuppositions - Abdul Murad, M.H.S. (2000)
This article discusses the relationship between modernisation, industrialisation, and globalisation. Globalisation is viewed as a consequence of modernisation, where modernisation is construed in both physical and intellectual terms. The intellectual and philosophical foundations of modernity is then explicated with reference to three major movements of thoughts in the eighteenth, nineteenth, and twentieth century, namely the Enlightenment, Hegelianism, and Logical Positivism. The article shows that a common thread running through these movements of thought was their emphasis on Rationality and Science, and how this has a levelling effects towards cultural convergence. The final part of the article looks at recent developments in postmodernist thought and discusses their possible implications for the 'epistemology of globalisation'. The article maintains that the postmodernist wholesale critique of modernist epistemology is unfounded, or needs qualification, and in its stark form could derail the project of globalisation through its derailment of the project of modernity.